항암화학요법을 받는 혈액종양환자의 치료목적에 따른 지지적 간호요구도 - 김수연; Soo-yeon Kim; 홍남수; Nam-soo Hong; 배상근; Sang-geun Bae (보건정보통계학회지, 2017)
Objectives: This study was performed to investigate the supportive care needs in accordance with therapeutic purposes of blood cancer patients. Methods: The study was conducted among 100 subjects treated as hematologic malignancies during 2016 in Daegu. The questionnaires included various disease-specific characteristics including Supportive Care Needs Survey-long form 59. We analyzed data using descriptive statistics, t-test, ANOVA and ANCOVA. Results: Of 6 domains in Supportive care needs survey (SCNS), the psychological domain showed the highest score followed by the patient care and support domain and the physical and daily living domain. The supportive care needs had a significant relationship with therapeutic purposes of blood cancer patients. The health system and information domain of supportive care needs was the highest in the patients who had been taking remission induction chemotherapy, while psychological domain was the highest in those who had been taking chemotherapy about consolidation therapy or relapse, and physical and daily living domain was the highest in the patients who had been taking chemotherapy before bone marrow transplantation. Conclusions: The patients with hematologic malignancy showed a distinct difference of supportive care needs depending on their therapeutic purposes. Patients` supportive care needs with hematologic malignancy should be assessed and used to provide patient-centered care.